Conservatory Musicians’ Temporal Organization and Self-Regulation Processes in Preparing for a Music Exam - Antonini Philippe, Roberta; Kosirnik, Céline; Vuichoud, Noémi; Clark, Terry; Williamon, Aaron; McPherson, Gary E. (Frontiers in Psychology, 2020)
Performing at the very highest levels requires rigorous preparation before the important performance. Musicians and especially music students encounter many challenges when preparing themselves for an important musical performance. This study sought to identify and analyze the context-specific temporal organization and self-regulation efforts that music students employ during their preparation period. Conservatory musicians were recruited from an Australian University Conservatorium. Thirteen conservatory musicians aged between 19 and 21 years old (M = 19,6; SD = 0,76) participated at the study. All musicians, through an elicitation interview, were asked to recall and reconstruct their preparation period, leading up to a performance exam. Elicitation interviews provided access to music students experiences by describing their general preparation. The results showed that conservatory musicians go through different phases (Phase 1: Choosing a piece; Phase 2: Piece discovery; Phase 3: Piece interpretation; Phase 4: Performance preparation). Self-regulatory efforts to prepare for a music performance exam vary from one musician to another. Organizational and disorganizational competencies, specific self-regulatory skills, seem not to be exploited by conservatory musicians. Also, during their preparation, most music students prefer technical and musical work than challenges such as playing in front of the public. Emotionally, conservatory musicians go through pleasant and unpleasant emotions depending on the phase of their preparation. Our results show that music students could benefit from advice on how to organize their preparation period well before an important performance takes place. Implications for conservatory musicians and teachers are discussed.